Incidence of superior etremity fractures in children at Ibnu Sina hospital Makassar 2017-2022 - Nurul Azizah An’naajiyyah; Jufri Latief; Evi Sulviani Gusnah; Dhedie Prasatia Sam; Ana Meliyana (Sean Institute, 2024)
A fracture is a disruption in the integrity of bone tissue typically resulting from external force. The upper extremity comprises five components: the shoulder, upper arm, forearm, wrist, and hand. Among these five locations, the upper arm, specifically the humerus, is the site where fractures occur most frequently, accounting for 15% of cases. This study aimed to ascertain the frequency of upper limb fractures in pediatric patients at Ibnu Sina Hospital Makassar from 2017 to 2022. The study employed descriptive methodologies with a cross-sectional design, utilizing secondary data extracted from medical records that satisfied the predefined inclusion criteria. This investigation was undertaken at Ibnu Sina Hospital Makassar from January 2017 to June 2022. The research data was acquired via direct documentation of information extracted from medical records. This study comprised a sample of 47 participants. The findings indicate that a significant proportion of the research participants were between the ages of 6 and 18 (93.62%), predominantly male (59.57%), with humerus fractures being the most common type (40.42%), and the majority of fractures being closed (89.36%).